Effects of Symmetry and Apparent Distance in a Parasagittal-Mirror Variant of the Rubber Hand Illusion Paradigm - de Silva, Jhana; Chen, Haiwen; Isaac, Sasha; White, Rebekah C.; Davies, Martin; Aimola Davies, Anne M. (Frontiers in Human Neuroscience, 2021)
When I see my face in a mirror, its apparent position (behind the glass) is not one that my own face could be in. I accept the face I see as my own because I have an implicit understanding of how mirrors work. The situation is different if I look at the reflection of my right hand in a parasagittal mirror (parallel to body midline), when my left hand is hidden behind the mirror. It is as if I were looking through a window at my own left hand. The experience of body ownership has been investigated using the rubber hand illusion (RHI). Several studies have shown that the RHI is elicited when the rubber hand is viewed in a frontal mirror. Our ‘proof of concept’ study was the first to combine use of a parasagittal mirror, and synchronous stroking of both a prosthetic hand (viewed in the mirror) and the participant’s hand, with a manipulation of the distance between the hands and of the symmetrical or asymmetrical arrangement of the two hands in front of and behind the mirror. The RHI was elicited using the parasagittal-mirror paradigm and the strength of the illusion depended, not on the physical distance between the hands, but on the distance between the apparent position of the prosthetic hand (viewed in the mirror) and the participant’s hand. The parasagittal-mirror paradigm may provide a distinctive way to assess whether competition for ownership depends on spatial separation between the prosthetic hand and the participant’s hand.